2014
DOI: 10.3390/molecules19079535
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolite Profiling of Curcuma Species Grown at Different Locations Using GC/TOF and UPLC/Q-TOF MS

Abstract: Curcuma, a genus of rhizomatous herbaceous species, has been used as a spice, traditional medicine, and natural dye. In this study, the metabolite profile of Curcuma extracts was determined using gas chromatography-time of flight mass spectrometry (GC/TOF MS) and ultrahigh-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF MS) to characterize differences between Curcuma aromatica and Curcuma longa grown on the Jeju-do or Jin-do islands, South Korea. Previous studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…Although samples were collected from different areas at various times, multivariate statistical analysis indicated that metabolic differences in plant species mainly depended on phylogenetic properties rather than environmental factors. Similar research revealed that differences in secondary metabolites of plants were affected by species rather than geological difference [31]. Twenty-four metabolites were considered as significantly different metabolites among the 6 plant families by variable importance in the projection (VIP) > 0.7 and p-value < 0.05 (Table 1).…”
Section: Chemotaxonomic Metabolite Profiling Of 62 Indigenous Korean mentioning
confidence: 82%
“…Although samples were collected from different areas at various times, multivariate statistical analysis indicated that metabolic differences in plant species mainly depended on phylogenetic properties rather than environmental factors. Similar research revealed that differences in secondary metabolites of plants were affected by species rather than geological difference [31]. Twenty-four metabolites were considered as significantly different metabolites among the 6 plant families by variable importance in the projection (VIP) > 0.7 and p-value < 0.05 (Table 1).…”
Section: Chemotaxonomic Metabolite Profiling Of 62 Indigenous Korean mentioning
confidence: 82%
“…A number of qualitative and quantitative analysis of curcuminoids using thin layer chromatography (Sotanaphun et al 2009), HPLC with UV or fluorescence detector (Jadhav et al 2007;Wichitnithad et al 2009;Cheng et al 2010;Li et al 2011), liquid chromatography-mass spectrometry (LC-MS) (Verma et al 2013), micellar electrokinetic chromatography (Watanabe et al 2000), and capillary electrophoresis (Lechtenberg et al 2004;Anubala et al 2014) have been reported in various Curcuma samples. In the chromatographic fingerprint analysis of Curcuma species, the reported analytical instruments used are HPLC (Li et al 2011;Lee et al 2014) and GC (Lee et al 2014;Hu et al 2014). HPLC with UV-vis detection was frequently employed for simultaneous determination of curcuminoids.…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed that the methanolic extract of C. longa rhizomes contains a mixture of compounds, especially sesquiterpene compounds such as germacrone, furanodiene, curcumene, turmerone, cedrene, curlone and β-elemene. Many of these compounds were major volatile components in essential oils and natural phytochemicals of C. longa known to have many biological activities (21,22).…”
Section: Gc-ms Analysis Of C Longa Rhizome Methanolic Extractmentioning
confidence: 99%